Design and simulation of a PI controller system with frequency response - Sadiq, Diyar A. S.; Saeed, Shivan H.; Muneer, Wasfiya A. (Science Journal of University of Zakho, 2016)
It is convenient to have a minimum number of parameters that are tuned to control a system.  Proportional-integral-derivative (PID) controllers have this specification and are now daily used in a different field of application especially in industrial control system.  To get the frequency response of such controller to any disturbance signal an appropriate design technique is needed.  Here a PI controller system is implemented and simulated using NI Multisim (13.0) software. We study the frequency response of a PI controller. The results and calculations show that the designed PI controller has very fast (above than 10 kHz) response to any disturbance. We show a large match between the simulation and the experimental part. A bode plot that give us the frequency response of the system has been calculated and measured. The implemented work is important for many applications especially in the field of atomic force microscopy (AFM), scanning tunneling microscopy (STM) and other industrial control system that need fast control.
Keywords: PID controller; PI; NI Multisim (version 13.0) software and frequency response; NI Multisim